Hubungan Antara Ketergantungan Emosional Dengan Romantic Jealous Pada Pasangan Menikah - Lailatul Ilmi; Tatik Mukhoyyaroh (State Islamic University (UIN) Ar-Raniry, 2018)
Background: Humans are social creatures who cannot live alone. Humans will always depend on someone else and also need help from others. Every human being also has the feeling of wanted to be loved and loving from their opposite sex. From these feelings, humans will make a relationship with someone they loved and make the it turns to the wedding stage. In every love affair as well as marriage relationship, individuals surely have a sense of jealousy. It is mostly caused by individuals are afraid of losing someone they really love. This fear can arise since individuals have emotional dependence with their partners. Individuals assume that only their partners who can make themselves happy. & Nbsp; Married couples would tend to be more protective of their partners. It is due to individuals’ sense of belonging who make them feel that their partner is a place to share complaints, bliss and sorrows, and also as a life-long friend. Those sense of dependence lead the individual to feel jealous. Objective: to find out the relationship between emotional dependence and romantic jealous. Method: a research using technical product moment correlation analysis with Likert’s scale model. The scale used is a modified jealous romantic scale from Damayanti (2010) and also a scale of emotional dependence modified from Socha (1995). The research subjects were married couples who lived in Manyar Sabrangan RT 02 RW 02 Street, Surabaya. It tooks 25% of the total 186 married couples into 50 married couples. Result: there is a relationship between emotional dependence and jealous romantic on married couples with the value of correlation analysis shows the value of 0.000<0.05 and has a positive correlation coefficient value of 0.395. To test the normality of emotional dependence scale of 0.061>0.05 and jealous romantic scale of 0130>0.05. Whereas for the linearity test of both variables is 0.852>0.05.Conclusion: there is a relationship between emotional dependence and jealous romantic on married couples. It means that the higher the emotional dependence, the higher the romantic jealous for married couples, and vice versa.